Plan tecnológico educativo para mejorar la comunicación oral en los niños con síndrome de asperger, Escuela Matilde Hidalgo, Durán 2021 - Ruiz Ramos, Jessica Elizabeth (2022)
The purpose of the research work is to develop an educational Technological Plan that allows improving oral communication in children with Asperger's syndrome at the Matilde Hidalgo school in the Duran canton, this has been done with the participation of experts who have collaborated with their opinions and experiences in the field of teaching and planning. This research work includes a statistical analysis section, where the Chi Square is handled, which allows the hypotheses raised in the document to be subjected to various tests at different contrasted frequency distributions in relation to some null hypothesis; Likewise, a non-experimental research design can be found here, with its type of research and mixed approach where the strengths of a qualitative and quantitative research were merged to respond to the needs. Likewise, for the present investigation, the educational community such as the teaching staff and parents of the “Matilde Hidalgo” Basic Education School was considered as the study population. This work shows clear evidence, with theoretical foundations related to Asperger's syndrome and the importance of special treatment of these infants and how currently the educational institutions of Ecuador are obliged to follow a series of guidelines established by the Ministry of Education regarding rights and duties of boys and girls who wish to access a better quality of education, especially for people with physical and emotional limitations and with intellectual capacities, promoting access to quality education based on inclusion. It also presents evidence of the great importance of guiding the training of teachers and parents in the application of the educational technology plan to develop oral communication skills in students with Asperger syndrome; Likewise, it is justified in practice, since it will contain special strategies for students, which will be a great visual support and will allow an alternative system of communication and understanding of the activities, which will be carried out in the classrooms.